Entre Exus e Minotauros: consumo, resistência e memória em representações de labirintos e encruzilhadas no cinema brasileiro - Agnelli, Vitor Gomes (2022)
This research is dedicated to the representations of labyrinths and crossroads in a selection of Brazilian cinematographic works that portray relations of violence, segregation and, at the same time, of resistance. We seek to study, from a selected set of contemporary national films, the violence that occurred since the slavery period and that persist in the history of Brazil materialized in several other forms of domination in modernity. For this, we work with authors who discuss decoloniality (such as BARBOSA, 2020; CAMPOS, 2020; MALDONADO-TORRES, 2019); the relations between modernity and consumption (as FONTENELLE, 2017; PESAVENTO, 1997; ROCHA, 1995); the construction of segregation walls (SAFATLE, 2016; DUNKER, 2015) and collective memories (NUNES, 2013; GONDAR, 2005; POLLAK, 1989). At all stages of the research, we relate the theories with the selected films: Um Lugar ao Sol (Gabriel Mascaro, 2009), The Good Manners (Juliana Rojas and Marco Dutra, 2017), Temporada (André Novais Oliveira, 2018), Estômago (Marcos Jorge, 2007) and Neighboring sounds (Kleber Mendonça Filho, 2012). The observation of the films and the path of the theoretical research made visible the strong tone of criticism of the forms of subjection and subordination present in works of contemporary Brazilian cinema, allowing us to affirm the existence of movements that match the logic promoted by the crossroads as a space of opening and encounter, even in the face of the labyrinths that continue to produce segregation.